Some Investigations of Auxin Effects on Rooting of Stem Cuttings of Forest Plants - Nanda, K. K.; Anand, V. K.; Kumar, Parshotam (Indian Forester, 1970)
This paper deals with the effect of 10 and 100 mg/l each of IAA, IBA, 2,4-D and NAA on seasonal changes in the rooting response of stem cuttings of forest plants. Anatomical structure of stem and seasonal changes in the mobilization of reserve food materials in a few cases were also studied. Experiment 1 deals with rooting trials on 102 broad-leaved species at 3-month intervals; experiment 2 on 9 species at 1-month intervals and experiment 3 with stem anatomy of some representative species. It was found that rooting occurred in 49 species only; on 26 without and 23 with auxin application. Of these 6 rooted throughout the year; 7 in 3 out of 4 plantings; 12 in two and 21 in one planting only. Stem cuttings of 53 species did not root at all. The easy-rooting species possessed multi-seriate vascular rays opening directly in the cortical region, while shy-rooting ones possessed a continuous ring of sclerenchyma surrounding the vascular bundles and which probably acted as a barrier to the penetration of water and emergence of roots. Stem cuttings of Populus nigra, Hibiscus rosa-sinensis and Ficus infutoria exhibited seasonal changes in rooting response closely corresponding with changes in starch content; low rooting corresponding with high and high rooting with low content of starch. Auxin effects on rooting are considered to be mediated through their effect on mobilization of starch caused by enhanced activity of hydrolyzing enzymes and is determined by the morpho-physiological status of the branches that govern the production of endogenous auxin.